Brand design in the era of 5g new media and its impact on consumers’ emotional experience - Li, Xinru (Frontiers in Psychology, 2022)
Brand design is an important part for enterprises to improve brand awareness and attract consumers. If a company wants to develop for a long time, it must have a good brand image. Good brand design can make a deep impression on consumers, thereby promoting purchase intention. With the advancement of technology and the development of the times, traditional brand design can no longer meet the needs of consumers, and the design of brand experience has gradually become a trend. Incorporating emotional experience into brand design can influence consumers' brand decisions, and can also make consumers resonate with the brand, which in turn generates purchase behavior. Today, the 5g new media era has quietly arrived. In this context, brand design is conducive to improving the reputation of the company and meeting the aesthetic needs of consumers. In the context of the 5g new media era, this paper studies and analyzes brand design and its impact on consumers' emotional experience, aiming to change the traditional brand design method and provide new ideas for brand design. In addition, combined with new media technology and mathematical relational model, the brand design method based on consumer emotion is discussed. The results show that the brand design method proposed in this paper can increase the emotional experience of consumers and improve the brand praise by 7.3%.